Reconstruction and Religious Freedom in the New Afghanistan - Nojumi, Neamat (The review of faith & international affairs, 2003)
Along with the economic and structural reconstruction of Afghanistan, the international community should commit to revitalizing the strong civil society that once flourished there. Afghanistan's religious history is one of peaceful coexistence and religious tolerance. Before the rise of the Taliban the affairs of the state were notmixed with the affairs of the mosque. Islamist fanaticism arose in Afghanistan only by external influence after the communist coup and Soviet invasion of the late 1970s. In order to reverse the harmful effects of Taliban rule, the international community should encourage discussions between the different religious groups in Afghanistan.